Pengembangan Sistem Manajemen Penilaian Anak Berkebutuhan Khusus (Studi Kasus : SLB Negeri 7 Jakarta) - Alif Prasetyo Aji; Achmad Arwan; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The development of children with special needs is influenced by parents and teachers in their schools. The problem that occurs in SLB Negeri 7 Jakarta is when the homeroom teacher wants to provide an assessment of student learning outcomes to parents of students. The subject teacher must give a score rack of the subjects taught to the class teacher or homeroom teacher then the homeroom teacher recapitulates the values ​​of each subject teacher and gives report cards to the parents of students. This is detrimental to the teacher and parents of students. The homeroom teacher must wait and recap the grades for each subject teacher. Parents of students are also disadvantaged because they only know the activities or grades of their children in each semester when taking report cards. Finally, parents of students can not do additional lessons to their children at home if there are subjects that are felt lacking by these students and also parents of students can not know the behavior of their children at school. Therefore an Assessment Management System was built to overcome these problems. In conducting this research, researchers used the waterfall method in developing software. In this study, 3 trial samples were produced for unit testing, one trial sample for integration testing and all functional requirements for validation testing. In addition, compatibility testing is performed to test whether the system can run in multiple browsers with a resolution that is suitable for the device used by the user and compatibility testing are 100% valid and can run on multiple browser. the results of unit testing, integration and validation are 100% valid.